Leadership Style and Library Digital Transformation of Private University Libraries in Southwest Nigeria (Jurnal Adabiya, 2024)
The twenty first century have seen a lot of innovation and advancement in technology. Old ways of doing things especially in academic libraries have been modified and transformed with technologies that make work faster and easier and makes service delivery more effective. These technologies and the way they work have been termed digital transformation. However, whatever digital transformation direction a library takes is a function of the leadership. With the above in mind, this paper investigated leadership style as a predictor of digital transformation in private university libraries in western Nigeria. The survey research of the correlational type was used. The population of the study are librarians from six private universities in South west Nigeria. The questionnaire was the instrument for data collection. Findings revealed that transformational leadership was the predominant style of leadership in private university libraries with mean of 24.12; KOHA was the most recent platform for DT in the libraries studied; level of digital transformation was revealed to be high. The hypothesis tested was rejected as leadership style was revealed to be significantly correlated with digital transformation in libraries.  It is recommended that management of libraries should foster a culture of continuous learning and innovation. Building on the predominant transformational leadership style identified, private university libraries should continue to encourage a culture of continuous learning and innovation among library staff.----------------------------------------------------------------------------------------------------------------Abad ke-21 telah menyaksikan banyak inovasi dan kemajuan dalam teknologi. Cara-cara lama dalam melakukan sesuatu, terutama di perpustakaan akademik, telah dimodifikasi dan diubah dengan teknologi yang membuat pekerjaan lebih cepat dan lebih mudah serta meningkatkan efektivitas penyampaian layanan. Teknologi-teknologi ini dan cara kerjanya disebut transformasi digital. Namun, arah transformasi digital yang diambil oleh perpustakaan adalah fungsi dari kepemimpinan. Dengan pemikiran tersebut, makalah ini menyelidiki gaya kepemimpinan sebagai prediktor transformasi digital di perpustakaan universitas swasta di Nigeria bagian barat. Penelitian survei tipe korelasional digunakan. Populasi penelitian adalah pustakawan dari enam universitas swasta di Nigeria bagian barat daya. Kuesioner adalah instrumen untuk pengumpulan data. Temuan mengungkapkan bahwa kepemimpinan transformasional adalah gaya kepemimpinan yang dominan di perpustakaan universitas swasta dengan nilai rata-rata 24,12; KOHA adalah platform terbaru untuk transformasi digital di perpustakaan yang diteliti; tingkat transformasi digital terungkap tinggi. Hipotesis yang diuji ditolak karena gaya kepemimpinan terbukti berkorelasi signifikan dengan transformasi digital di perpustakaan. Disarankan agar manajemen perpustakaan mendorong budaya pembelajaran dan inovasi yang berkelanjutan. Berdasarkan gaya kepemimpinan transformasional yang dominan, perpustakaan universitas swasta harus terus mendorong budaya pembelajaran dan inovasi yang berkelanjutan di kalangan staf perpustakaan.